Construction of a High-Density Genetic Map Based on SLAF Markers and QTL Analysis of Leaf Size in Rice - Wen, Yi; Fang, Yunxia; Hu, Peng; Tan, Yiqing; Wang, Yueying; Hou, Linlin; Deng, Xuemei; Wu, Hao; Zhu, Lixin; Zhu, Li; Chen, Guang; Zeng, Dali; et al. (Frontiers in Plant Science, 2020)
Leaf shape is an important agronomic trait for constructing an ideal plant type in rice, and high-density genetic map is facilitative in improving accuracy and efficiency for quantitative trait loci (QTL) analysis of leaf trait. In this study, a high-density genetic map contained 10,760 specific length amplified fragment sequencing (SLAF) markers was established based on 149 recombinant inbred lines (RILs) derived from the cross between Rekuangeng (RKG) and Taizhong1 (TN1), which exhibited 1,613.59 cM map distance with an average interval of 0.17 cM. A total of 24 QTLs were detected and explained the phenotypic variance ranged from 9% to 33.8% related to the leaf morphology across two areas. Among them, one uncloned major QTL qTLLW1 (qTLL1 and qTLLW1) involved in regulating leaf length and leaf width with max 33.8% and 22.5% phenotypic variance respectively was located on chromosome 1, and another major locus qTLW4 affecting leaf width accounted for max 25.3% phenotypic variance was mapped on chromosome 4. Fine mapping and qRT-PCR expression analysis indicated that qTLW4 may be allelic to NAL1 (Narrow leaf 1) gene.